Recent Progress on Copper-Mediated Directing-Group-Assisted C(sp2)–H Activation - Shang, Ming; Sun, Shang-Zheng; Wang, Hong-Li; Wang, Ming-Ming; Dai, Hui-Xiong (Synthesis, 2016)
Considerable progress has been made in the area of copper-mediated C(sp2)–H functionalization reactions with the assistance of chelating directing groups. Due to the advantages of copper catalysts such as low cost, low toxicity, and unique reactivity compared to precious metals, they have attracted more and more attention in organic synthesis. This review summarizes recent advances in this field according to the classification of directing groups.1 Introduction2 The Pyridine Directing Group 2.1 C–N Bond Formation2.2 C–O Bond Formation2.3 C–S Bond Formation2.4 C–C Bond Formation2.5 C–CN Bond Formation2.6 C–Halogen Bond Formation3 Bidentate Directing Groups3.1 8-Aminoquinoline3.2 (2-Pyridyl)Sulfonyl and Picolinic Acid3.3 Amide-Oxazoline Auxiliary3.4 2-(Pyridin-2-yl)isopropylamine (PIP Amine)3.5 2-Aminopyridine 1-Oxide4 Conclusions and Outlook
Keywords: C–H bond functionalization; copper; pyridine; bidentate directing group